Nanofibrous material from hyaluronan derivatives preserving fibrous structure in aqueous environment - Skuhrovcová, Kristýna; Kotzianová, Adéla; Bardoňová, Lenka; Židek, Ondřej; Toropitsyn, Evgeniy; Vágnerová, Hana; Čápová, Aneta; Dostálová, Kateřina; Hermannová, Martina; Pokorný, Marek; Velebný, Vladimír (Carbohydrate polymers, 2022)
Nanofibrous materials produced from natural polymers have wide range of potential uses in regenerative medicine. This paper focuses on preparation of nanofibrous layers produced from intentionally hydrophobized derivatives of hyaluronan, which is known for its ability to promote wound healing. This structural modification of hyaluronan expands the range of potential uses of this promising material, which is otherwise limited due to the hydrophilic nature of hyaluronic acid. The aim of this research was preparation of nanofibrous material that would retain its fibrous structure and dimensional stability even after getting into contact with an aqueous medium, which is impossible to achieve with layers composed solely of native hyaluronan. As a result, such material would be able to retain its breathability and good mechanical properties when both dry and wet. Furthermore, all prepared materials were proved non-toxic for cells. This self-supporting nanofibrous matrix can be used as a scaffold, or porous wound dressing.